Functional expression of a novel ginsenoside Rf binding protein from rat brain mRNA in Xenopus laevis oocytes - Choi, S; Jung, SY; Ko, YS; Koh, SR; Rhim, H; Nah, SY (AMER SOC PHARMACOLOGY EXPERIMENTAL THERAPEUTICS, 2002)
We have shown that ginsenoside Rf (Rf) regulates voltage-dependent Ca2+ channels through pertussis toxin (PTX) sensitive G proteins in rat sensory neurons. These results suggest that Rf can act through a novel G protein-linked receptor in the nervous system. In the present study, we further examined the effect of Rf on G protein-coupled inwardly rectifying K+ (GIRK) channels after coexpression with size-fractionated rat brain mRNA and GIRK1 and GIRK4 (GIRK1/4) channel cRNAs in Xenopus laevis oocytes using two-electrode voltage-clamp techniques. We found that Rf activated GIRK channel in a dose-dependent and reversible manner after coexpression with subfractions of rat brain mRNA and GIRK1/4 channel cRNAs. This Rf-evoked current was blocked by Ba2+,a potassium channel blocker. The size of rat brain mRNA responding to Rf was about 6 to 7 kilobases. However, Rf did not evoke GIRK current after injection with this subfraction of rat brain mRNA or GIRK1/4 channel cRNAs alone. Other ginsenosides, such as Rb-1 and Rg(1), evoked only slight induction of GIRK currents after coexpression with the subfraction of rat brain mRNA and GIRK1/4 channel cRNAs. Acetylcholine and serotonin almost did not induce GIRK currents after coexpression with the subfraction of rat brain mRNA and GIRK1/4 channel cRNAs. Rf-evoked GIRK currents were not altered by PTX pretreatment but were suppressed by intracellularly injected guanosine- 5'-( 2-O-thio) diphosphate, a nonhydrolyzable GDP analog. These results indicate that Rf activates GIRK channel through an unidentified G protein-coupled receptor in rat brain and that this receptor can be cloned by the expression method demonstrated here.
Keywords: ACTIVATED K+-CHANNEL; POTASSIUM CHANNEL; CA2+ CHANNELS; ATP RECEPTOR; CLONING; CELLS; SYSTEM